Association of Impaired Reactive Aldehyde Metabolism with Delayed Graft Function in Human Kidney Transplantation. (23rd December 2018) - Wijermars, Leonie G. M.; Schaapherder, Alexander F.; George, Thomas; Sinharoy, Pritam; Gross, Eric R.
Abstract : Delayed graft function is an early complication following kidney transplantation with an unclear molecular mechanism. Here we determined whether impaired reactive aldehyde metabolism is associated with delayed graft function. Human kidney biopsies from grafts with delayed graft function were compared with grafts that did not develop delayed graft function by Ingenuity gene pathway analysis. A second series of grafts with delayed graft function (n = 10 ) were compared to grafts that did not develop delayed graft function (n = 10 ) by measuring reactive aldehyde metabolism, reactive aldehyde-induced protein adduct formation, and aldehyde dehydrogenase (ALDH) gene and protein expression. In the first series of kidney biopsies, several gene families known for metabolizing reactive aldehydes, such as aldehyde dehydrogenase (ALDH), aldo-keto reductase (AKR), and glutathione-S transferase (GSTA), were upregulated in kidneys that did not develop delayed graft function versus those that did. In the second series of kidney grafts, we focused on measuring aldehyde-induced protein adducts and ALDH enzymatic activity. The reactive aldehyde metabolism by ALDH enzymes was reduced in kidneys with delayed graft function compared to those that did not (37 ± 12 ∗ vs. 79 ± 5 μ g/min/mg tissue, ∗ P < 0.005, respectively). ALDH enzymatic activity was also negatively correlated with length of hospital stay after a kidney transplant. Together, our study identifies a reduced ALDH enzymatic activity with kidneys developing delayed graft function compared to those that did not. Measuring ALDH enzymatic activity and reactive aldehyde-induced protein adducts can potentially be further developed as a biomarker to assess for delayed graft function and recovery from a kidney transplant.